Flammability and thermal degradation of poly (lactic acid)/polycarbonate alloys containing a phosphazene derivative and trisilanollsobutyl POSS. (19th November 2015) - Jiang, Peng; Gu, Xiaoyu; Zhang, Sheng; Sun, Jun; Xu, Riwei; Bourbigot, Serge; Duquesne, Sophie; Casetta, Mathilde
Abstracts: This work reports our recent efforts on improving the flame retardancy and thermal stability of biodegradable poly (lactic acid) (PLA) which is usually produced from corn and sugar beets. Hexa-(phosphaphenanthrene-methyl-(p-hydrobenzal)-amino-phenoxyl)-cyclotriphosphazene (HPHAPC) was synthesized by the classic Kabachnik-Fields reaction, and was then incorporated into PLA/polycarbonate (PC) alloys by melt blending. The flammability evaluation by limiting oxygen index (LOI), vertically burning (UL-94) and cone calorimeter tests has indicated that the LOI value can reach up to 31.5 and UL-94 grade can pass V-0 by the presence of only 3 wt% HPHAPC and 3 wt% polyhedral oligomeric silsesquioxane (POSS). The thermal behavior characterization by thermo-gravimetric analysis (TGA) and differential scanning calorimetry (DSC) shows that the char formation of PLA/PC alloys can be significantly enhanced by the presence of HPHAPC/POSS. The evolved gas of the alloys was analyzed by Fourier transform infrared spectroscopy-TGA (FTIR-TGA) and pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS). Char morphology was observed by scanning electronic microscopy (SEM). It is demonstrated that HPHAPC can react with POSS during processing to form an intumescent char structure. It is proposed that the degradation products of HPHAPC/POSS can capture free radicals in the gas phase and enhance char formation in the condensed phase. Graphical abstract: Highlights: A novel phosphorus/nitrogen contained flame retardant HPHAPC was synthesized. The fire performance of PLA/PC was synergistically improved by HPHAPC and POSS. The flame retardant mechanism of HPHAPC/POSS in PLA/PC was proposed and discussed.